PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN MENULIS TEKS BERITA (Studi pada mata pelajaran Bahasa Indonesia Kelas VIII SMPNegeri 1 Pulau Pinang) - Ulfa Yulistina (UNIB Press, 2020)
This study aims to describe the application of Cooperative Integrated Reading and Composition (CIRC) learning models to improve students' critical thinking skills, write news texts. This research was conducted using Classroom Action Research (CAR) and quasi-experimental. The subjects of the study were students of class VIII in semester one of the 2019/2020 school year at SMPN 1 Pulau Pinang. For quasi-experimental samples of classes 8.1 and 8.3. Data collection methods in this study used observation sheets for the CIRC model and critical thinking skills, as well as tests to measure the ability to write student news texts. For data analysis the average score analysis and t-test were used. From the results of the study, it shows that the application of the CIRC learning model can improve the ability to think critically and write news texts for Grade VIII students of SMPN 1 Pulau Pinang.